Nanomaterials Based on Natural Polyphenol Compounds in the Surgical Treatment of Breast Cancer. Issue 1 (13th June 2022) - Zhu, Chenlei
Abstract: As a new type of lymphatic tracer, nano carbon has been widely used. This study mainly explores the application of nanomaterial preparation based on natural polyphenol compounds in the surgical treatment of breast cancer. The operation methods included total / near total breast ectomy, lobectomy and isthmectomy. All the patients met the above criteria after screening. The patients in the two groups were interviewed before operation and informed consent was given. The preoperative examination was actively improved and the contraindications were excluded. According to the intraoperative lymph node black staining, the lymph nodes in each area were divided into three groups: black staining in area II, non-black staining in area II, black staining in area II, non-black staining in area I, black staining in area IV and non-black staining in area IV. The patients and their families were informed before the operation, and the preventive lateral lymph node dissection was performed according to the freezing condition during the operation. Each patient expressed his understanding and signed the informed consent for the operation. During the operation, the breast gland was fully exposed after the breast pseudocapsule was free. All patients used nano-carbon injection during the operation. 0.2 ml nano carbon was injected into the gland at multiple points. After the injection, the injection point was pressed with gauze, and the black staining of the gland was observed after waiting for 3–5 min. The "refined dorsal membrane dissection" and "1 + X" method were used to preserve parabreast glands in situ . The black stained lymph nodes in the central area (confirmed by postoperative pathology) were set as sentinel lymph nodes (SLNs), and the remaining lymph nodes in the dissected tissues were set as non-SLNs. There were 101 sides of cN0 microcarcinoma, 97 sides were detected with black stained lymph nodes, the median number was 7 (1–27), 63 sides had central region metastasis, the false negative rate was 14.29%, the sensitivity was 85.71%, the specificity was 100%, and the accuracy was 91.89%. This study is helpful to promote the application of nano carbon in the operation of CNO differentiated breast cancer.